Faith under Construction: Dialectical Qur’anic Inquiry into Ethics, Power, and Institutional Responsibility in Islamic Education - Syarifudin, Aip; Aspandi, Ade; Abdul Zalil, Muhammad; Hasan Basuni, Kiki Mustaqimah (ADDIN, 2026)
The collapse of a dormitory building at Al-Khoziny Islamic boarding school symbolizes a deeper moral decline within the institutional structures of Islamic education. This study utilizes a Qur’anic dialectical inquiry to examine the intersection of faith, ethics, and power in shaping institutional responsibility. Employing a library research methodology, the analysis focuses on the Qur’anic concepts of al-‘adl (justice), al-amanah (trust), and al-ihsan (excellence) as ethical frameworks for institutional governance. Classical tafsir (interpretation), hadith compilations, and contemporary literature on Islamic educational ethics are critically reviewed to construct a dialogical interpretation between textual revelation and modern institutional realities. The findings demonstrate that the moral accountability of Islamic institutions intrinsically linked to their adherence to divine ethical mandates. The dialectical analysis further reveals that neglecting al-‘adl and al-amanah results not only in administrative fragility but also in the erosion of social trust. Al-ihsan emerges as a transformative principle that urges continuous moral reconstruction within institutional systems. Rather than assigning blame, this study highlights the Qur’an’s call for introspective reform, suggesting that physical failure should be interpreted as an ethical discourse on “responsibility before God and society”. This paper proposes a Qur’anic institutional ethics model centered on social accountability, encouraging Islamic educational entities to balance faith, power, and responsibility within an integrated moral structure.